Sweet corn seeds coating with hexane plant extracts for controlling maize weevil (Sitophilus zeamais Motschulsky) and their effect on seed qualities - Pumnuan, J.; Sikhao, P.; Sarapothong, K.; Nameea, D.; Doungnapa, T.; Lakyat, A.; Thipmanee, K. (My University, 2023)
The insecticidal activity of hexane crude extracts from star anise, Illicium verum Hook.f. (HS) and clove, Syzygium aromaticum (L.) Merrill & Perry (HC) coated on sweet corn seeds, Zea mays var. rugosa against maize weevil, Sitophilus zeamais Motschulsky were evaluated in laboratory conditions. The sweet corn seeds were coated with 1, 3 and 5% hexane extracts and stored at 4°C for the period of 6 months. The insecticidal property and the effect on seed germination were evaluated after period of 2, 4 and 6 months. Various concentrations of extracts and fipronil insecticide (positive control) were tested for their efficiencies and compared with the coating agent (negative control). The result of this study showed that all hexane extract treatments gave low effectiveness to kill the adult insects, nevertheless it could completely inhibit progeny emerging. Besides, 1% of HS and HC application by using this film seed coating method presented moderate effect on seed germination after period of 6 months as it exhibited the seed germination in laboratory percentages of more than 60%. However, insect mortalities caused by hexane extracts were significantly different compared with the positive and negative control groups.
Keywords: clove; hexane extract; progeny inhibition; seed germination; star anise